All Days 2000
DOI: 10.2118/58976-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drag-Reducing Agents in Multiphase, Oil/Gas Horizontal Flow

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAn experimental study has been carried out in a 36-m long, 10-cm diameter in horizontal multiphase system. Oil with a viscosity of 2.5 cP was used as the liquid phase and carbon dioxide was the gas phase. The effect of drag reducing agents (DRA) on average pressure drop, maximum pressure drop and slug characteristics for superficial liquid and gas velocities of 0.5 to 1.5 m/s and 2 to 12 m/s, respectively, was studied at DRA concentrations of 0, 20 and 50 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In general, the drag reduction increased with increasing U SL and decreased with increasing U SG . This result contradicts the finding of Kang and Jepson (2000) and Sylvester and Brill (1976), but is consistent with the present experiments. In general, the drag reduction was higher in the 2.54 cm pipe (maximum of 63%) than in the 9.53 cm pipe (maximum of 48%).…”
Section: Literature Reviewsupporting
confidence: 75%
“…In general, the drag reduction increased with increasing U SL and decreased with increasing U SG . This result contradicts the finding of Kang and Jepson (2000) and Sylvester and Brill (1976), but is consistent with the present experiments. In general, the drag reduction was higher in the 2.54 cm pipe (maximum of 63%) than in the 9.53 cm pipe (maximum of 48%).…”
Section: Literature Reviewsupporting
confidence: 75%
“…They obtained a 35% drag reduction rate. Kang and Jepson [16,17] and Daas et al [18] found the drag reduction rate of gas-liquid two-phase flow varied from 30% to 50% for the concentration of the high polymer increasing from 10 ppm to 50 ppm, respectively. For higher superficial gas velocity, the drag reduction rate drops from 50% to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kang and Jepson [3,[5][6][7][8] have published laboratory test results for drag reduction in multiphase flow. They have noted that DRA works not only ftictional pressure drop but also accelerational pressure drop in slug flow regime.…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of DRA depends on a lot of parameters such as types of DRA, temperature, pH, DRA concentration, oil viscosity, pipe diameter, liquid and gas flow rates, pipe roughness, composition oil, and so on [8], Therefore, it is suggested that laboratory test for drag reduction should be performed due to the technical and economic aspects before DRA is used in the field.…”
Section: Introductionmentioning
confidence: 99%